Pengaruh Investment Assets dan Capital Expenditure terhadap Financial Sustainability - Sarah Siburian; Etty Murwaningsari (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
This study aims to analyze the effect of investment assets and size of board on financial sustainability in companies operating in the Basic Materials and Consumer Non-Cyclicals sectors. Financial sustainability refers to a company's ability to maintain stable financial conditions over the long term and fulfill its operational obligations without experiencing financial distress. This study employs a quantitative approach using a purposive sampling method, involving 82 companies listed on the Indonesia Stock Exchange (IDX). The sampling technique was based on several criteria, namely: companies that were listed on the Indonesia Stock Exchange during the 2022–2024 period, used the Indonesian Rupiah as their reporting currency, and had data that met the research and data processing requirements. The data were processed using EViews 10. The data were analyzed using panel data regression to examine the relationships among variables. The results indicate that investment assets have a positive and significant effect on financial sustainability. However, capital expenditure does not have a significant effect on financial sustainability. These findings suggest that effective management of investment assets and an optimal board size can strengthen a company's long-term financial sustainability. In contrast, the magnitude of capital expenditure does not directly contribute to improving financial stability.